RELEVANSI PERAN GEREJA DALAM MEMBENTUK KARAKTER GENERASI MUDA DI ERA DIGITAL: SEBUAH KAJIAN TEOLOGI PRAKTIS - Nirma; Defiana Momba (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
The development of the digital era poses serious challenges to the character formation of young Christians, as digital technology often displaces faith and moral values that should be shaped by the church. This study aims to: (1) analyze the condition of youth character formation in the digital era from a practical theological perspective, and (2) analyze the strategic role of the church in forming the character of young people in the digital era. The research employs a qualitative approach using a literature study method. Data sources consist of relevant theological and Christian education journals. Data were analyzed descriptively and analytically within a practical theological framework. The findings indicate that today's youth face identity crises, spiritual decline, and exposure to digital content contrary to Christian values. The church is called to be adaptively present through contextual ministry based on partnership, needs, and technology, while also synergizing with families to build a solid spiritual habitus. This study concludes that the relevant and strategic role of the church is decisive in forming Christian-charactered youth amid the tide of digital change.